Synthesis and characterization of reduced graphene oxide / TiO2 nanocomposites as high performance photocatalyst / Betty Chang Yea Sze - Chang, Betty Yea Sze (2013)
A simple single stage approach, based on the hydrothermal technique, has been introduced to synthesize reduced graphene oxide-titanium dioxide (RGO/TiO2) nanocomposites. The titanium dioxide (TiO2) nanoparticles are formed at the same time as the graphene oxide (GO) is reduced to graphene. The triethanolamine (TEA) used in the process has two roles. It acts as a reducing agent for the GO as well as capping agent allowing the formation of titanium dioxide nanoparticles with a narrow size distribution (~20 nm). Transmission Electron Microscopy (TEM) micrographs show that the nanoparticles are uniformly distributed on the reduced graphene oxide (RGO) nanosheet. Thermogravimetric Analysis (TGA) analysis shows the nanocomposites have an enhanced thermal stability over the original components. The potential application for this technology was demonstrated by the use of RGO/TiO2 nanocomposites in the photodegradation of methylene blue (MB). A significant enhancement in the photodegradation rate of MB under natural solar light was observed with the as-prepared RGO/TiO2, compared to the commercial P25 and pure TiO2 synthesized using the same method. This is due to the excellent adsorptivity of dyes performed by RGO (~8 times more powerful) and also because of the reduced electron-hole pair recombination demonstrated by the as-prepared RGO/TiO2. Besides, the nanocomposites exhibit high recyclability. Overall, this work could provide new insights into the fabrication of a TiO2-carbon composite as high performance photocatalysts and facilitate their application in the environmental protection issues.